Overall survival in patients with advanced melanoma who received Nivolumab versus investigator’s choice chemotherapy in CheckMate 037: a randomized, controlled, open-label phase III trial - Larkin, James; Hassel, Jessica C. (Journal of clinical oncology, 2018)
Purpose: Until recently, limited options existed for patients with advanced melanoma who experienced disease progression while receiving treatment with ipilimumab. Here, we report the coprimary overall survival (OS) end point of CheckMate 037, which has previously shown that nivolumab resulted in more patients achieving an objective response compared with chemotherapy regimens in ipilimumab-refractory patients with advanced melanoma. Patients and Methods: Patients were stratified by programmed death-ligand 1 expression, BRAF status, and best prior cytotoxic T-lymphocyte antigen-4 therapy response, then randomly assigned 2:1 to nivolumab 3 mg/kg intravenously every 2 weeks or investigator’s choice chemotherapy (ICC; dacarbazine 1,000 mg/m2 every 3 weeks or carboplatin area under the curve 6 plus paclitaxel 175 mg/m2 every 3 weeks). Patients were treated until they experienced progression or unacceptable toxicity, with follow-up of approximately 2 years. Results: Two hundred seventy-two patients were randomly assigned to nivolumab (99% treated) and 133 to ICC (77% treated). More nivolumab-treated patients had brain metastases (20% v 14%) and increased lactate dehydrogenase levels (52% v 38%) at baseline; 41% of patients treated with ICC versus 11% of patients treated with nivolumab received anti-programmed death 1 agents after randomly assigned therapy. Median OS was 16 months for nivolumab versus 14 months for ICC (hazard ratio, 0.95; 95.54% CI, 0.73 to 1.24); median progression-free survival was 3.1 months versus 3.7 months, respectively (hazard ratio, 1.0; 95.1% CI, 0.78 to 1.436). Overall response rate (27% v 10%) and median duration of response (32 months v 13 months) were notably higher for nivolumab versus ICC. Fewer grade 3 and 4 treatment-related adverse events were observed in patients on nivolumab (14% v 34%). Conclusion. Nivolumab demonstrated higher, more durable responses but no difference in survival compared with ICC. OS should be interpreted with caution as it was likely impacted by an increased dropout rate before treatment, which led to crossover therapy in the ICC group, and by an increased proportion of patients in the nivolumab group with poor prognostic factors.
Published online July 03, 2017
Gesehen am 24.02.2020